Collision energy dependence of moments of net-kaon multiplicity distributions at RHIC - STAR Collaboration (Physics Letters B, 2018)
Fluctuations of conserved quantities such as baryon number, charge, and strangeness are sensitive to the correlation length of the hot and dense matter created in relativistic heavy-ion collisions and can be used to search for the QCD critical point. We report the first measurements of the moments of net-kaon multiplicity distributions in Au+Au collisions at sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV. The collision centrality and energy dependence of the mean (M), variance (σ2), skewness (S), and kurtosis (κ) for net-kaon multiplicity distributions as well as the ratio σ2/M and the products Sσ and κσ2 are presented. Comparisons are made with Poisson and negative binomial baseline calculations as well as with UrQMD, a transport model (UrQMD) that does not include effects from the QCD critical point. Within current uncertainties, the net-kaon cumulant ratios appear to be monotonic as a function of collision energy.
Keywords: dept.phy; peer-reviewed